FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ABORTUS - Jannah, Raudhatul; Dewi, Vonny Khresna; Tunggal, Tri; Laili, Fitria Jannatul (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: Abortion is a health problem that impacts maternal morbidity and mortality worldwide. Abortion can cause complications that lead to maternal and infant death. The incidence of abortion at Pambalah Batung Regional Hospital in 2024 reached 5.73%. Several factors associated with abortion include maternal age, parity, and history of abortion. Objective: To find out the factors related to abortion incidents at Pambalah Batung Regional Hospital in 2024 Methods: This research design was an observational analytic study with a case-control approach. The sampling technique used simple random sampling with a sample ratio of 139:139. The instruments used were secondary data. Data analysis used the Chi-Square test and Odds Ratio. Results: A total of 139 mothers (50.0%) had experienced abortion. A total of 92 mothers (33.1%) were at risk (<20 years or >35 years). A total of 29 mothers (46.4%) had high-risk parity (1 child or >3 children). A total of 99 mothers (35.6%) had a history of abortion. Conclusion: There was a correlation between maternal age (P 0,002, OR 2,211), parity (P 0,012, OR 1,845), and history of abortion (P 0,001, OR 2,372) with the incidence of abortion at Pambalah Batung Hospital. Pambalah Batung Regional Hospital can develop strategies and evaluations to reduce the incidence of abortion.